Perceived Thai Restaurant Service Quality among Generation Z in Bangkok - Sirieawphikul, Chanutwat; Anekjumnongporn, Pongsavake (Thammasat Journal, 2026)
This study aimed to assess the level of perceived service quality of Thai restaurants among Generation Z consumers in Bangkok and compare these perceptions across demographic characteristics of this population. Data were collected via a structured questionnaire administered to a stratified random sample of 806 respondents aged 18-28 years, drawn proportionally from six urban zones. Data analysis comprised descriptive statistics and inferential tests. The findings were as follows; 1) Generation Z in Bangkok reported a relatively high overall perception of service quality, ranking the SERVQUAL dimensions in descending order of importance as Reliability; Responsiveness; Assurance/Safety; Empathy/Service Care; and Tangibles/Reputation/Image. 2) Significant differences in perceived service quality emerged across household-income groups (p < .05), indicating that income level influences how Generation Z evaluates service quality. Moreover, no statistically significant differences were found in perceived service quality with respect to gender, age, educational level, field of study, or family residence.